(untitled) (Clinics, 2013)
There are two main reasons why sperm may be absent from semen. Obstructive azoospermia is the result of a blockage in the male reproductive tract; in this case, sperm are produced in the testicle but are trapped in the epididymis. Non-obstructive azoospermia is the result of severely impaired or non-existent sperm production. There are three different sperm-harvesting procedures that obstructive azoospermic males can undergo, namely MESA (microsurgical epididymal sperm aspiration), PESA (percutaneous epididymal sperm aspiration), and TESA (testicular sperm aspiration). These three procedures are performed by fine-gauge needle aspiration of epididymal fluid that is examined by an embryologist. Additionally, one technique, called TESE (testicular sperm extraction), is offered for males with non-obstructive azoospermia. In this procedure, a urologist extracts a piece of tissue from the testis. Then, an embryologist minces the tissue and uses a microscope to locate sperm. Finding sperm in the testicular tissue can be a laborious 2- to 3-hour process depending on the degree of sperm production and the etiology of testicular failure. Sperm are freed from within the seminiferous tubules and then dissected from the surrounding testicular tissue. It is specifically these situations that require advanced reproductive techniques, such as ICSI, to establish a pregnancy. This review describes eight different lab processing techniques that an embryologist can use to harvest sperm. Additionally, sperm cryopreservation, which allows patients to undergo multiple ICSI cycles without the need for additional surgeries, will also be discussed.